An Electrochemical and Raman Spectroscopy Study of the Surface Behaviour of Mononuclear Ruthenium and Osmium Polypyridyl Complexes Based on Pyridyl‐ and Thiophene‐Based Linkers. Issue 24 (17th June 2013) - Halpin, Yvonne; Logtenberg, Hella; Cleary, Laura; Schenk, Stephan; Schulz, Martin; Draksharapu, Apparao; Browne, Wesley R.; Vos, Johannes G.
Abstract: The utility of a thiophene anchor unit as an alternative for thiols in the immobilisation of ruthenium and osmium complexes on gold and platinum is examined with special attention focused on the relative contributions of physi‐ and chemisorption of the complexes and the chemical stability of the thiophene anchoring unit. The redox and spectroscopic properties of the ruthenium(II) and osmium(II) complexes are described in solution and the effect of surface immobilisation examined through a combined electrochemical and surface‐enhanced Raman spectroscopic study. A key finding is that although the thiophene unit is involved in surface anchoring it also undergoes chemical reactions with the gold surface as demonstrated by Raman spectroscopy. Abstract : The synthesis and immobilisation of a series of ruthenium and osmium compounds with novel pyridine and thiophene linking groups are reported. The monolayers are studied both electrochemically and by surface‐enhanced Raman spectroscopy.